Efficacy of Immune Checkpoint Inhibitors in Rare Tumours: A Systematic Review - Petrelli, Fausto; Consoli, Francesca; Ghidini, Antonio; Perego, Gianluca; Luciani, Andrea; Mercurio, Paola; Berruti, Alfredo; Grisanti, Salvatore (Frontiers in Immunology, 2021)
Background: Rare cancers, as defined by the European Union, occur in fewer than 15 out of 100,000 people each year. The International Rare Cancer Consortium defines rare cancer incidence as less than six per 100,000 per year. There is a growing number of reports of the efficacy of immune checkpoint inhibitor (ICI) therapy in patients with rare tumours, and hence, we conducted a comprehensive review to summarise and analyse the available literature. Methods: A literature search of PubMed was performed on January 31, 2021, using the following ICI names as keywords: ipilimumab, tremelimumab, cemiplimab, nivolumab, pembrolizumab, avelumab, atezolizumab and durvalumab. Studies with patients with rare tumours who were being treated with ICIs were included. We plotted the overall response rate against the corresponding median survival across a variety of cancer types using linear regression. Results: From 1,255 publications retrieved during the primary search, 62 publications we selected (with a total of 4,620 patients). Only four were randomised trials. A minority were first-line studies, while the remaining were studies in which ICIs were delivered as salvage therapy in pretreated patients. There was a good correlation between response rate and overall survival (Spearman R2 >0.9) in skin cancers, mesothelioma and sarcomas. Conclusions: Treatment of advanced-stage rare tumours with ICI therapy was found to be associated with significant activity in some orphan diseases (e.g. Merkel cell carcinoma) and hepatocellular carcinoma. Several ongoing prospective clinical trials will expand the knowledge on the safety and efficacy of ICI therapy in patients with these rare cancers.